A framework for controlling multiple industrial robots using mobile applications - Alvarado, Daniela; Asif, Seemal (SciDoc Publishers, 2021)
Purpose: Over the last few decades, the development of the hardware and software has enabled the application of advanced systems. In the robotics field, the UI design is an intriguing area to be explored due to the creation of devices with a wide range of functionalities in a reduced size. Moreover, the idea of using the same UI to control several systems arouses a great interest considering that this involves less learning effort and time for the users. Therefore, this paper will present a mobile application to control two industrial robots with four modes of operation. Design/methodology/approach: The smartphone was selected to be the interface due to its wide range of capabilities and the MIT Inventor App was used to create the application, whose environment is supported by Android smartphones. For the validation, ROS was used since it is a fundamental framework utilised in industrial robotics and the Arduino Uno was used to establish the data transmission between the smartphone and the board NVIDIA Jetson TX2. In MIT Inventor App, the graphical interface was created to visualize the options available in the app whereas two scripts in python were programmed to perform the simulations in ROS and carry out the tests. Findings: The results indicated that the use of the sliders to control the robots is more favourable than the Orientation Sensor due to the sensibility of the sensor and human limitations to hold the smartphone perfectly still. Another important finding was the limitations of the autonomous mode, in which the robot grabs an object. In this case, the configuration of the Kinect camera and the controllers has a significant impact on the success of the simulation. Finally, it was observed that the delay was appropriate despite the use of the Arduino UNO to transfer the data between the Smartphone and the Nvidia Jetson TX2. Originality/value: The following points show the contributions of this paper to the robotic field. • Developed a robust application combining four different modes of functionality. • Create a program with an intuitive interface and simple use that allows controlling different robotics arms with just one UI. • Evaluate the applicability of the simulated industrial robots in ROS since the projects must be tested in a framework before implementing it in real robots.
Keywords: Programming; Robot Control; Smartphone Application; Manipulators; Controllers